29.0k views
5 votes
Find average rate of change for given function from x =-3 to x=1

Find average rate of change for given function from x =-3 to x=1-example-1
User Ptfaulkner
by
4.5k points

1 Answer

6 votes

Solution

- The formula for the rate of change of a function is:


\begin{gathered} m=(f(b)-f(a))/(b-a) \\ where, \\ b,a\text{ are the }x-values\text{ of the function }f(x) \end{gathered}

- We can apply the formula as follows:


\begin{gathered} a=1,b=-3 \\ f(-3)=-3 \\ f(1)=5 \\ \\ \therefore m=(f(-3)-f(1))/(-3-1)=(-3-5)/(-3-1)=-(8)/(-4) \\ \\ m=2 \\ \end{gathered}

Final Answer

The rate of change is 2

User Shrikant Mavlankar
by
4.8k points